Arab spring, IS and democracy - Akhmetova, Elmira (New Straits Times Press (NSTP), 2015)
The emergence of the so-called Islamic State of Iraq and Syria – ISIS - at the tail end of Arab Spring confirmed once again that the import of Western democracy to the Middle Eastern and North Africa (MENA) is not a cure to the deeply-rooted sociopolitical problems of that region. Numerous Muslim thought leaders and governments have denounced the ISIS brutalities as being anti-Islamic and antithetical to the core principles of the religion. Yet, the self-styled leader of ISIS, Abu Bakr al-Baghdadi, claims global authority of the Muslim ummah in the manner of the caliphs of old.